EKSPERIMENTASI MODEL PROBLEM BASED LEARNING DAN MODEL PEMBELAJARAN MISSOURI MATHEMATICS PROJECT DITINJAU DARI SIKAP SISWA TERHADAP MATEMATIKA PADA MATERI PERSAMAAN DAN PERTIDAKSAMAAN LINEAR SATU VARIABEL KELAS VII SMP NEGERI SE-KABUPATEN BELITUNG - Irnistisia, Firna; Kusmayadi, Tri Atmojo; Riyadi, Riyadi (Journal of Mathematics and Mathematics Education, 2016)
Abstract: The objective of this research was to investigate the effect of the  learning models on the learning achievement in mathematics viewed from students attitude toward mathematics. The learning models compared were the problem based learning (PBL) type, the cooperative learning model of the missouri mathematics  project (MMP) type, and the direct learning model. This research used the quasi experimental research. Its population was all of the students in Grade VII of State Junior Secondary Schools of Belitung regency in Academic Year 2014/2015. The samples of the research were taken by using the stratified cluster random sampling technique and consisted of 285 students. They were grouped into three classes, namely: 95 students in Experimental Class 1, 96 students in Experimental Class 2, and 94 students in Control Class. The instruments to gather the data were test of achievement in learning mathematics and the students attitude toward mathematics questionnaire. The proposed hypotheses of the research were analyzed by using the two way analysis of  variance with unbalanced cells. The results of the research were as follows. 1) The cooperative learning model of the PBL type results in a better learning achievement in Mathematics than the cooperative learning model of the MMP type  and  the  direct  learning  model,  the cooperative  learning  model of  the  MMP type results in a better learning achievement in Mathematics than the direct learning model. 2)  The  students  with  the high attitudes toward mathematics have a better learning achievement in mathematics than those with the moderate students attitudes toward mathematics and  those with  the low students attitudes toward mathematics, the students with the moderate attitudes toward mathematics have a better learning achievement in mathematics than those with the low students attitudes toward mathematics. 3) There was an interaction the aforementioned learning models and the categories students attitude toward mathematics on the learning achievement in mathematics of the students.Keywords: PBL, MMP, and students attitude toward mathematics.